Conkin & Stromberg, Heritage and Challenge - the History and Theory of History. Himmelfarb, the New History and the Old - Pennington, Loren (Teaching History: A Journal of Methods, 1991)
Heritage and Challenge, first published in 1971 and now revised, is intended for use as a textbook and is really two books in one. The first half, by Stromberg, is a history of history, while the second half, by Conkin, is an examination of the philosophy of history; only the chapter on "Recent Trends" and the brief epilogue are collaborative efforts. Stromberg’s six chapters on historians from ancient times to about 1960 are an analytical critique rather than a mere summary. His basic argument is that modem historical consciousness, which he defines as the ability to understand change, did not begin to emerge until the Enlightenment, and reached its full flower only in the nineteenth century-the "Golden Age" of history.